Software process improvement initiative in medium size IT organization: a case study - Mohammad Zarour; Mamdouh Alenezi (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
IT organizations are striving to develop software solutions that meet customer needs as well as their business goals. Software organization scontinuously improve their software development practices for faster time-to-market and better software quality. The success factors to conduct process improvement initiatives are documented in the literature, but their effect and existences differ from one place to another. Hence, as the culture and organizational behavior in developing software varies across the world, it becomes interesting to report and discuss local experiences in differentregions. The experience gained in this empirical study differs from that gained in the previous work in the sense that it was the organization that initiated this initiative and this ensures the top management commitment in conducting the process improvement initiative. We have used CMMI continuous representation and SCAMPI Class C appraisal method to conduct the appraisal. In this empirical study, most of the success factors are met toconduct the process improvement initiative, including: Staff involvement and high staff morale. Several process pitfalls have been identified; an interesting one is that adopting powerful case tools is not enough to control the development process if they are not fully used.